PENGARUH PENGGUNAAN TEKNIK PEMODELAN BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA SMP NEGERI 12 PADANG - Ulya, Ulya; Gani, Erizal; Abdurahman, Abdurahman (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose of this research wasto describe the influence of modeling technique that supported by the series picture media through the ability of writing the eksplanasi text by the VII gradestudents in SMPNegeri12 Padang. The type of this research is quantitative with experiment method and the research planning that used was one group pretest-posstest.Based on the results of data analysis it was concluded the following three points.First, the skills of writing eksplanasi textby the VII grade students in SMPNegeri12 Padang before using modeling technique that support the series picture media have the average that include Enough(60,94)in qualifications (C). Second, the skills of writing eksplanasi textby the VII grade students in SMPNegeri12 Padang using modeling technique received the series picture media have the average that include Enough(80,38) in qualificationsis good (B). Third, based on the result of uji-t, concluded that there was effects of modeling technique that supported the series picture media towards the skills of eksplanasi textby the VII grade students in SMPNegeri12 Padang because thitung> ttabel (8,34 > 1,70).Â Kata kunci: pengaruh, teknik pemodelan berbantuan media gambar berseri, teks eksplanasi.